Screening and prevention of anticoagulant resistance development in house mice – A review - Blažić, Tanja; Jokić, Goran; Đedović, Suzana (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2020)
Unrestricted use of anticoagulants has resulted in rodents developing resistance to them. This has caused a series of problems regarding reduction in rodent populations, which has further implicated great economic losses and a serious threat to the health of people and domestic animals. The popular global trend currently is to control rodent populations by applying the least possible amounts of chemicals, which on the other hand implies that several coactive alterantive measures need to be applied in an eff ort to reduce rodent numbers to an acceptable economic level. On the other hand, knowledge of the genetic structure of rodent populations has become an important set of information desirable to have before setting off to apply rodenticides in practice, so as to prevent ineff ective use of rodenticides and prevent further spreading of resistant rodent populations. The latest trend of using combinations of low-dose anticoagulant baits requires further research as their eff ects on susceptible populations are known but their impact on resistant animalsis still not clear.
Keywords: Mus musculus; rodenticides; anticoagulants; resistance; vkorc1